A Technical/Strategic Paradigm for Online Executive Education. (January 2017) - Smith, Marlene A.; Keaveney, Susan M.
ABSTRACT: This article discusses the development and delivery of online courses for the executive education audience. The goal is to introduce a new framework, the technical/strategic paradigm, that will help educators to identify the pedagogical needs of disparate executive groups and adjust their online course development plans accordingly. We describe how four key elements of online courses (course structure, content‐based learning materials, assignments, and learning assessment) should be fashioned in a way that honors the technical or strategic focus of the learning environment. How the technical/strategic paradigm molds well with many different types of executive educational audiences and settings is illustrated. Course developers seeking advice on how to put these ideas into practice will find lists of resources and implementable recommendations. Ultimately, we argue that some of the pitfalls that faculty experience when transitioning from a traditional business school environment to an online executive education environment can be attributed to a misunderstanding of the degree to which students expect technical versus strategic content.